Analisis Inovasi Strategi Dalam Meningkatkan Entrepreneurship Mahasiswa STIE Bima - Mukminin, Amirul; Heriwibowo, Dedy; Salam, Abdul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This research was conducted to see how the form of strategic innovation carried out by STIE Bima in increasing Student Entrepreneurship at the College of Economics (STIE) Bima. The research focused on SMT VII students as a research sample with the consideration that these students had participated in the entire series of Entrepreneurial activities organized by the Bima College of Economics. From the results of the qualitative analysis, it was found that there were three strategic innovations carried out by STIE Bima in increasing the Entrepreneurship of its students, namely Entrepreneur Courses, Entrepreneur Events, and Entrepreneur KKN-T. From the results of the SWOT analysis, the three programs are in diagram I which means they contain alternative strategies that are, STIE Bima can take advantage of existing opportunities by optimizing their strengths or strengths as an effort to increase student entrepreneurshipThis research was conducted to see how the form of strategic innovation carried out by STIE Bima in increasing Student Entrepreneurship at the College of Economics (STIE) Bima. The research focused on SMT VII students as a research sample with the consideration that these students had participated in the entire series of Entrepreneurial activities organized by the Bima College of Economics. From the results of the qualitative analysis, it was found that there were three strategic innovations carried out by STIE Bima in increasing the Entrepreneurship of its students, namely Entrepreneur Courses, Entrepreneur Events, and Entrepreneur KKN-T. From the results of the SWOT analysis, the three programs are in diagram I which means they contain alternative strategies that are, STIE Bima can take advantage of existing opportunities by optimizing their strengths or strengths as an effort to increase student entrepreneurship